MATEMÁTICA E MÚSICA: UMA ABORDAGEM PARA EXPLORAR CONCEITOS MUSICAIS PARA ENSINAR MATEMÁTICA NO ENSINO MÉDIO E FUNDAMENTAL - Santos, Rodovlas Fabiano dos (2015)
Music is without any doubt one of the main ways to express culture, gender and personal tastes. Western music in general has the same musical basis which has its core in simple mathematical concepts. This study aims to bring mathematical concepts to high and elementary school students through the history of music. This essay proposes a literature review about the importance and the contributions of Pitagoras in the construction of Diatonic Scale and the influence that pitagorian studies exert in the Equal Tempered Scale, used nowadays. This paper is based in official documents such as PCN and PCNEM (National Curricular Parameters and National Curricular Parameters of High School) and curricular guidelines about the study of Mathematics allying mathematical subjects to daily life concepts, in this case, musical concepts. Activities that can be reproduced by Mathematics teachers even when the teacher does not have advanced musical knowledge are studied in this paper, for example, studying fractions aiming to build a monochord with the program Geogebra exploring sound concepts described by exponential and trigonometric functions.